Analisis Kecurangan Laporan Keuangan dengan Kualitas Audit sebagai Variabel Moderasi pada Perusahaan LQ45 di Bursa Efek Indonesia - Husnul Mufidah; Umi Muawanah; Sugeng (Lembaga Teewan Journal Solutions, 2026)
Financial statement is intentional misrepresentation of financial reports by hiding important information, misstating balances, or making mistakes in applying generally accepted accounting principles (GAAP). The purpose of this research among others are: i) to analyze how financial stability, nature of industry, auditor change, CEO education, CEO duality, and political connection influences financial statement fraud; ii) to analyze how financial stability, nature of industry, auditor change, CEO education, CEO duality, and political connection influences financial statement fraud with audit quality as a moderating variable. This research is quantitative research and hypothesis testing used in this research uses Moderated Regression Analysis (MRA) which is tested with the help of SPSS version 25 software. This research uses secondary data obtained from the Indonesia Stock Exchange website. The population of this research is LQ45 companies listed on the Indonesia Stock Exchange that publish financial reports during the 2022-2024 period. The sample of this research is 28 LQ45 companies listed on the Indonesia Stock Exchange. The results of the study show that (i) financial stability, nature of industry, auditor change, CEO education, CEO duality, and political connection significantly influence financial statement fraud. The direction of influence shows that financial stability, auditor change, CEO duality, and political connection have a positive effect, while nature of industry and CEO education have a negative effect. (ii) audit quality weakens the impact of financial stability, auditor change, CEO duality, and political connection on financial statement fraud, but strengthens the negative impact of industry type and CEO education on financial statement fraud.